Impact of pre- and post-emergence herbicides on weed control, physiology, yield, and economics of sesame (Sesamum indicum L.): IMPACT OF PRE- AND POST-EMERGENCE HERBICIDES ON SESAME - B NAVYASHIKA; D JACOB; SHEEJA K RAJ; P SHALINI PILLAI; V MINI (Journal of Oilseeds Research, 2026)
A field experiment was conducted at the Onattukara Regional Agricultural Research Station, Kayamkulam, Kerala, to evaluate the impact of pre- and post-emergence herbicides on weed management, physiological traits, yield, and economics in sesame (Sesamum indicum L.). The study was laid out in a randomized block design with nine treatments and three replications. The major weed present in the experimental field was Melochia corchorifolia (chocolate weed). The results indicated that weed management practices significantly improved growth attributes, physiological parameters, and yield compared to the weedy check. The highest dry matter production (7.87 g/plant), crop growth rate (2.244 g/m²/day), weed control efficiency (82.35%), seed yield (478 kg/ha), and haulm yield (1177 kg/ha) were recorded in T7 (mechanical weeding with a wheel hoe weeder at 15 and 30 DAS). At 60 DAS, the lowest weed density was observed in T4 [pre-emergence (PE) application of pendimethalin at 500 g/ha followed by carfentrazone-ethyl at 20 g/ha at 25 DAS] (31.82 plants/m²), which was statistically at par with T7 (mechanical weeding with a wheel hoe weeder at 15 and 30 DAS) (33.26 plants/m²). However, integrated weed management involving PE application of pendimethalin at 2 DAS followed by wheel hoe weeding at 25 DAS (T6) resulted in the highest benefit-cost ratio (2.09).